LA Fiction Anthology : Southland Stories by Southland Writers - Brantingham, John; Gale, Kate (Book collections on Project MUSE., 2016)
"Los Angeles may be best known as the hub of the film and television industry, but this collection of short fiction proves that beyond the beach and the glamour of Hollywood there is much more that makes the City of Angels special. Featuring an eclectic mix of fiction from a variety of talented literary minds--including TC Boyle, Ron Carlson, Judith Freeman, Percival Everett, and more--this anthology defies genre or easy categorization. Topics explored range from the deeply personal, such as a lesbian couple's loss of a child and the reaction of a young man to a natural disaster, to the larger-than-life, including a vivid tale of a robot-infested dystopian Long Beach. This allows the creativity and vivacity of the Los Angeles literary scene to be put on display, with a powerful sense of place as the core of this ambitious and insightful project"--